Republic of Serbia Capital Market Development - World Bank Group (World Bank, Washington, DC, 2019)
Capital markets in Serbia are shallow and relatively underdeveloped. The only market segment that functions comparatively well is the government bond market. The contribution of capital markets to financing the economy is limited. The private sector is not making use of non-government bond markets for its financing needs, given easy access to affordable bank loans in Serbia’s bank-dominated financial system. Until recently there was no IPO activity since 1940, symptomatic of Serbia’s shallow public and private equity markets. This Technical Note was prepared by Zsolt Bango (Senior Financial Sector Specialist, World Bank), Sonia Marie Cattarinussi Iacovella (Senior Financial Sector Specialist, World Bank) and Eddy Rodriguez (World Bank Consultant) in the context of the Serbian Capital Market Assessment mission in Belgrade during June 2018 led by Zsolt Bango. The primary objective of the mission was to conduct a diagnostic of the Serbian capital market, with a view to make recommendations for capital market development. The note contains technical analysis and detailed information underpinning the assessment’s findings and recommendations. The report was written under the guidance of Gunhild Berg (Senior Financial Sector Specialist, World Bank) and Johanna Jaeger (Senior Financial Sector Specialist, World Bank) and the team received excellent support from Tanya Konidaris (Senior Financial Sector Specialist, World Bank).